Creative music making through composition workshop for higher education educators: an experiential learning - Salleh, Marzelan; Mohamed Razali, Camellia Siti Maya (Universiti Pendidikan Sultan Idris, 2020)
This study looked into a way experiential learning was incorporated into a music course by having students participate in a workshop led by a subject matter expert. In the workshop, Passepartout Duo’s role as subject matter experts in the music field ensures an ideal experiential learning environment for composition music students to immerse themselves in order to develop new skills and knowledge. Passepartout Duo is a piano and percussion duo based in Germany, who performs and composes contemporary music. Passepartout Duo members are Nicoletta Favari (piano & keyboard) and Christopher Salvito (drums and percussion). The music composition workshop which ran for two consecutive days was presented in an informal group context introducing contemporary music. Participants and observers of the workshop included Malaysian music students of higher education institutions and professional composers. Participating composers composed original music pieces and worked together and were directly involved with Passepartout Duo in the creative processes required in creating their own music composition and the culmination of the workshop was a concert featuring music compositions from participating composers performed by the duo. Students attending the workshop were found to better grasp musical concepts, be more creative, and have a peek into the career as a composer. Implementing workshops into the music course also maximised learning forstudents and ensured the efficient development of the course.